Technologies for energy use of waste - Biernat, Krzysztof; Dziołak, Paulina Luiza; Samson-Bręk, Izabela (Studia Ecologiae et Bioethicae, 2011)
The aim of this paper is to show municipal and organic waste as an alternative source of energy and the benefits which can bring their energy use. These benefits concern both environmental reasons, as well as freedom from conventional energy sources and increasing energy security. The article discusses the biogas technology and plasma technology as the most promising waste to energy technologies.